Environmentally friendly construction technologies selection criteria in the Arctic - A. A. Kuzmenkov; A. V. Kaychenov (Vestnik MGSU)
Introduction. The paper substantiates the relevance of creating and improving digital tools for complex scientific research and development work based on the information model of a construction object at all stages of the life cycle. The research focuses on environmentally safe (green) construction in the northern and Arctic regions. The purpose of the study is to substantiate a set of criteria for “green” for the northern and Arctic regions of the Russian Federation on the basis of logically interrelated models: a design model, a full-scale model, mathematical models and a digital twin model. The main criteria include energy efficiency and environmental safety of buildings.Materials and methods. The objects of the study are two twin buildings designed and built according to the programme of scientific research in the Republic of Karelia and the Murmansk region. The objects are identical, but the conditions of their functioning are different. The methodology of complex scientific research for each stage of the life cycle of objects is proposed. The methods of comparative analysis and the method of expert assessments were used, as well as the methods presented in the normative and technical documents of the technical regulation system of the Russian Federation related to the technological aspects of construction.Results. Four groups of basic construction criteria for the northern and Arctic regions of the Russian Federation are defined: external environment; internal environment; materials and technologies; energy efficiency. The Research Information Model (RIM) was developed as a tool for comprehensive scientific research in the field of construction technologies in the northern and Arctic regions. The practical implementation of the results of the study at the two above-mentioned facilities, including digital monitoring of the condition of the facilities for two years (2021–2023), is considered. Prospects for the continuation of the research are determined.Conclusions. The necessity of the development is justified and the expediency of using the developed information model of research is confirmed by the example of two constructed objects. The experience of using the main blocks of the model and digital monitoring of the condition of objects for two years has confirmed the expediency of using information modelling and continuing research to improve construction technologies in the northern and Arctic regions.